Load Balance: Energy Efficient Routing Protocol in Wireless Sensor Network - A. Mohamed Divan Masood; S. K. Muthusundar (Institute of Advanced Engineering and Science, 2018)
Energy consumption is one of the major issue in Wireless Sensor Network (WSN) which reduces the lifetime of the network. In this developed work an Cluster based Energy Efficient Routing Protocol (CBEERP) , which is gathering the sensor hubs in the system into clusters, in this manner it productively decreased the flooding traffic during discover the routing. The proposed CBEERP will balance the Energy in the Group by using some second order nodes. The reinforcement High effective hubs replace the cluster head after the cluster reaches to its threshold energy level. This CBEERP will help the effectiveness and lifetime of the system.